Numbers of Purkinje Cell with Increasing Age-A Post Mortem Study (Faridpur Medical College Journal, 2011)
The change in the number of Purkinje cells with increasing age is evident especially in disorders of fine movement, equilibrium, hypotonia, postural changes, and disturbances of voluntary movement. The present study was done to see the changes in the number of Purkinje cells per square mm in different age groups of Bangladeshi people. This cross sectional descriptive type of study was designed and done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2010, which was performed on the cerebellum of 28 Bangladeshi people, collected during autopsy examination of unclaimed dead bodies from Department of Forensic Medicine. Paraffin blocks of cerebellum were cut at 5mm thickness and stained with routine Harris' Haematoxylin and Eosin (H & E) stain. Estimation of number of Purkinje cell was done by using the counting circle and examined under the light microscope. The mean ± SD of number of Purkinje cell was 160.71 ± 24.47 in group A (Age 20-29 years) and 152.20 ± 6.49 in group D (age> 50 years), the mean reduction was 2.5% per decade. Histological studies revealed the number of Purkinje cell per square mm decreased with age which was statistically significant and further cytological study of Purkinje cell with larger sample size is recommended. Key words: Purkinje cell; Cerebellum. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9209 FMCJ 2011; 6(2): 92-94